Large Conductance Switching in a Single-Molecule Device Through Room Temperature Spin-Dependent Transport - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2016)
Controlling the spin of electrons in nanoscale electronic devices is one of the most promising topics aiming at developing devices with rapid and high density information storage capabilities. The interface magnetism or spinterface resulting from the interaction between a magnetic molecule and a metal surface, or vice versa, has become a key ingredient in creating nanoscale molecular devices with novel functionalities. Here, we present a single-molecule wire that displays large (>10000%) conductance switching by controlling the spin-dependent transport under ambient conditions (room temperature in a liquid cell). The molecular wire is built by trapping individual spin crossover FeII complexes between one Au electrode and one ferromagnetic Ni electrode in an organic liquid medium. Large changes in the single-molecule conductance (>100-fold) are measured when the electrons flow from the Au electrode to either an α-up or a β-down spin-polarized Ni electrode. Our calculations show that the current flowing through such an interface appears to be strongly spin-polarized, thus resulting in the observed switching of the single-molecule wire conductance. The observation of such a high spin-dependent conductance switching in a single-molecule wire opens up a new door for the design and control of spin-polarized transport in nanoscale molecular devices at room temperature. © 2015 American Chemical Society.